2022
DOI: 10.3390/genes13112026
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Selection Signatures Underlying Domestication Inferred from Genome-Wide Copy Number Variations in Chinese Indigenous Pigs

Abstract: Single nucleotide polymorphism was widely used to perform genetic and evolution research in pigs. However, little is known about the effect of copy number variation (CNV) on characteristics in pigs. This study performed a genome-wide comparison of CNVs between Wannan black pigs (WBP) and Asian wild boars (AWB), using whole genome resequencing data. By using Manta, we detected in total 28,720 CNVs that covered approximately 1.98% of the pig genome length. We identified 288 selected CNVs (top 1%) by performing F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Genome-wide comparison of copy number variation between Wannan black pigs (WBP) and Wannan black pigs (AWB) was carried out using genome-wide resequencing data. The results showed that genes such as Ndn , Tmod3 , Sfrp1 and Smyd3 were related to muscle development ( Zhang et al, 2022 ). It can up-regulate the expression of adipogenic factors, moderately delay muscle development, promote adipogenesis, and play an important role in microfilament length regulation and myofibril assembly ( Zhao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide comparison of copy number variation between Wannan black pigs (WBP) and Wannan black pigs (AWB) was carried out using genome-wide resequencing data. The results showed that genes such as Ndn , Tmod3 , Sfrp1 and Smyd3 were related to muscle development ( Zhang et al, 2022 ). It can up-regulate the expression of adipogenic factors, moderately delay muscle development, promote adipogenesis, and play an important role in microfilament length regulation and myofibril assembly ( Zhao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Manta was used for CNV identification and Paragraph for genotyping the variants in each sample. The methods for obtaining high-quality CNVs were based on our previous study ( 29 ). PLINK software v.1.90 ( 30 ) was used to determine frequency, with visualization conducted using R (v4.2.0).…”
Section: Methodsmentioning
confidence: 99%
“…The WIF1 was found as selected in pigs in our previous study [29]. Based on an association analysis, WIF1 was found to regulate the ear size of pigs and dogs [29,67]. Feed efficiency is one of the main factors determining production costs in the pig industry.…”
Section: Patterns Of Selection Signaturesmentioning
confidence: 98%
“…WNT inhibitory factor 1 (WIF1) could inhibit activity of the Wnt/β-catenin pathway that can regulate proliferation and differentiation in many tissues, such as controlling the growth of connective tissue by regulating the connective tissue growth factor [66]. The WIF1 was found as selected in pigs in our previous study [29]. Based on an association analysis, WIF1 was found to regulate the ear size of pigs and dogs [29,67].…”
Section: Patterns Of Selection Signaturesmentioning
confidence: 99%
See 1 more Smart Citation